Emerging Business Development Model in the Sports Industry - Ali Ghanbari; Mohammad Soltanhoseini; Zahra Halajpoor; zahra Borgheyan (Archives in Sport Management and Leadership)
Emerging businesses significantly impact the sports industry, playing a vital role in company formation and entrepreneurship. The aim of this study was to emerging business model development in the sports industry. The research method is based on the multi-grounded approach in terms of practical purpose and qualitative data. The participants included 14 experts in sports marketing, sports management, technology, and entrepreneurship participated. The research tool was a semi-structured interview. The interviewing process continued until theoretical saturation (14 people) was reached. Validation was done using the triangulation approach. The final research model was organized into 4 main axes: 1- Influential factors (social factors, environmental factors, economic factors, cultural factors, political factors, technology and foresight), 2- Challenges and obstacles (educational constraints, environmental constraints, financial constraints, attitudinal and cultural constraints, legal constraints, technology and market constraints), 3- Strategies (financial strategies, security technologies, culture, laws and regulations, education, new technologies, innovation and dissemination and promotion), 4- Consequences (market-related consequences, customer-related consequences, financial consequences, branding and technological consequences). The emerging business development model in the sports industry allows entrepreneurs and managers to comprehensively assess all factors impacting their businesses and create tailored strategies. This model identifies threats and opportunities, addresses challenges, facilitates training programs, and fosters effective collaboration networks, promoting innovation and idea exchange, while ensuring growth and sustainability.